An open source reservoir and sediment simulation framework for identifying and evaluating siting, design, and operation alternatives. (February 2021) - Wild, Thomas B.; Birnbaum, Abigail N.; Reed, Patrick M.; Loucks, Daniel P.
Abstract: This paper introduces PySedSim, an open-source, object-oriented, Python-based, daily time step river basin simulation screening model for flow, sediment, and hydropower in networks of reservoirs and river channels. The model enables users to explore representations of four key concerns relevant to the selection and evaluation of alternative reservoir configurations: 1) management approaches to improve the passage of sediment through and around reservoirs to avoid storage capacity loss and downstream ecological impacts; 2) search for flexible and adaptive reservoir operating policies designed to achieve multiple objectives; 3) alternative design features such as dam gates, which are necessary to enable ecologically-focused reservoir features; and 4) uncertainties associated with hydroclimatic drivers and sediment processes. PySedSim is intended to support deliberative decision-making and design processes. We highlight PySedSim's functionality by demonstrating its use in a real decision context focused on identifying siting, design, and operation alternatives for the proposed Sambor mega Dam in Cambodia. Graphical abstract: Image 1 Highlights: Reservoir design and operation alternatives improve sediment passage. Flexible problem formulation improves understanding of tradeoffs and alternatives. Evaluating sediment, ecology, and hydropower together yields synergistic insights. PySedSim supported iterative deliberation of alternatives to Sambor Dam (Cambodia).